Coated stainless steel as bipolar plate material for anion exchange membrane fuel cells (AEMFCs). (6th January 2020) - Proch, Sebastian; Stenström, Mikael; Eriksson, Lennart; Andersson, Jan; Sjöblom, Gustaf; Jansson, Anna; Westlinder, Jörgen
Abstract: Low-temperature anion-exchange membrane fuel cells (AEMFCs) are gathering increased attention because they facilitate the use of non-precious metal catalysts, which might drastically reduce costs compared to low-temperature proton exchange membrane fuel cells (PEMFCs). Metallic, e.g., stainless steel, bipolar plates (BPPs) present a cost-efficient solution for this type of cell. However, anodic film formation at high positive potentials (approx. +1.5 V vs. RHE) on uncoated metals/stainless steels leads to high interfacial contact resistance (ICR) of the BPP once exposed to such a potential. A potential of +1.5 V vs. RHE is commonly reached under local and global hydrogen starvation, which rules out the use of uncoated metals in AEMFCs. We have investigated the ICR change and oxide film formation of several materials under simulated fuel cell operating conditions and found that suppression of anodic film formation and, in turn, low ICRs can be achieved by carbon coating of stainless steels. Graphical abstract: You shall not pass! High contact resistances between the components of an AEMFC leads to ohmic losses and decreased efficiencies. Unfortunately, many metals and alloys exhibit oxide film growth at high positive potentials (purple question marks) and, in turn, high contact resistances. This behavior can be mitigated by carbon-coating of the metallic substrate. Image 1 Highlights: Fuel starvation (local and global) leads to high anodic potentials at both electrodes. metallic bipolar plates grow anodic (oxide) films increasing contact resistance and, in turn, ohmic losses during operation. carbon coating slows down anodic film formation and preserves low contact resistance over longer time frames.